In Vitro Modeling of Bile Acid Processing by the Human Fecal Microbiota - Martin, Glynn; Kolida, Sofia; Marchesi, Julian R.; Want, Elizabeth; Sidaway, James E.; Swann, Jonathan R. (Frontiers in Microbiology, 2018)
Bile acids, the products of concerted host and gut bacterial metabolism, have important signaling functions within the mammalian metabolic system and a key role in digestion. Given the complexity of the mega-variate bacterial community residing in the gastrointestinal tract, studying associations between individual bacterial genera and bile acid processing remains a challenge. Here, we present a novel in vitro approach to determine the bacterial genera associated with the metabolism of different primary bile acids and their potential to contribute to inter-individual variation in this processing. Anaerobic, pH controlled batch cultures were inoculated with human fecal microbiota and treated with individual conjugated primary bile acids (500 µg/ml) to serve as the sole substrate for 24 hours. Samples were collected throughout the experiment (0, 5, 10 and 24 hours) and the bacterial composition was determined by 16S rRNA gene sequencing and the bile acid signatures were characterized using a targeted ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) approach. Data fusion techniques were used to identify statistical bacterial-metabolic linkages. An increase in gut bacteria associated bile acids was observed over 24 hours with variation in the rate of bile acid metabolism across the volunteers (n = 7). Correlation analysis identified a significant association between the Gemmiger genus and the deconjugation of glycine conjugated bile acids while the deconjugation of taurocholic acid was associated with bacteria from the Eubacterium and Ruminococcus genera. A positive correlation between Dorea and deoxycholic acid production suggest a potential role for this genus in cholic acid dehydroxylation. A slower deconjugation of taurocholic acid was observed in individuals with a greater abundance of Parasutterella and Akkermansia. This work demonstrates the utility of integrating compositional (metataxonomics) and functional (metabonomics) systems biology approaches, coupled to in vitro model systems, to study the biochemical capabilities of bacteria genera within complex ecosystems. Characterizing the dynamic interactions between the gut microbiota and the bile acid pool enables a greater understanding of how variation in the gut microbiota influences host bile acid signatures, their associated functions and their implications for health.